Obtenção de compostos semissintéticos do triterpeno 3β,6β,16β-tri-hidroxilup-20(29)-eno isolado de Combretum leprosum e avaliação da atividade citotóxica - Silva Filho, Carlos José Alves da (2024)
The triterpene 3β,6β,16β-trihydroxylup-20(29)-ene (4) is the main secondary metabolite isolated from Combretum leprosum, a plant widely dispersed in Northeast Brazil and with diverse ethnopharmacological uses. For this substance, anticancer, antimicrobial, antinociceptive, leishmanicidal, anti-inflammatory and healing activities are described. In this work, we describe the obtaining of 42 chemical derivatives of 4 obtained through reactions of acylation, oxidation, oximation, dehydration, formation of hydrazone and imidazole salts, which were planned based on our available reagents and information from the literature. Of the 42 results obtained, seven have already been described (21, 23, 24, 25, 26, 27 and 31), with compounds 25, 26, 27 and 31 previously obtained by our research group. The cytotoxic activity of 23 results was evaluated against three human tumor cell lines, HCT-116 (Human Colon), PC-3 (Prostate) and SNB-19 (Glioblastoma), and one non-tumor cell line, HEK293T (kidney epithelial cells human). Of these, the most active were triterpene 4 (IC50 9.10-16.56 µg/mL) and the results 3β,16β-dihydroxy-6-oxolup-20(29)-ene (23) (IC50 6.14-13.99 µg/mL) and 3β,6β-dihydroxy-16β-propionyloxylup-20(29)-ene (53) (IC50 8.75-15.26 µg/mL) for tumor cell lines PC-3, SNB-19 and HCT-116. The two semi-synthetic compounds showed better biological activity compared to the natural product 4. However, they showed toxicity towards healthy HEK293T cells, with an IC50 variation of 5.343 and 14.55 µg/mL. In this way, a semi-synthesis strategy for providing bioactive compounds from natural products has been demonstrated to be an important tool in the search for molecules with pharmacological potential.